2017
DOI: 10.3390/molecules22050733
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Glucuronidation and Sulfation of ε-Viniferin, a Resveratrol Dimer, in Humans and Rats

Abstract: ε-Viniferin is a resveratrol dimer that possesses antioxidant or anti-inflammatory activities. However little is known about the metabolism of this oligostilbene. This study was thus undertaken as a first approach to identify and characterize the metabolites of ε-viniferin and to describe the kinetic profile of their appearance in humans and rats. The glucuronides and sulfates of ε-viniferin were first obtained by chemical hemi-synthesis and were fully characterized by UPLC-MS and NMR spectroscopy. Then, ε-vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(54 reference statements)
2
13
0
1
Order By: Relevance
“…The mass spectra obtained from plasma and tissue analysis showed the presence of ε-viniferin phase-II metabolites: glucuronide and sulphate conjugates. These metabolites, previously characterized in our laboratory, were identified as being V1G, V2G, V3G and V4G for glucuronides and V1S, V2S, V3S, and V4S for sulphates ( Figure 1 ) [ 16 ]. The plasma and tissue concentration-time profiles of total glucuronides and of total sulphates are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mass spectra obtained from plasma and tissue analysis showed the presence of ε-viniferin phase-II metabolites: glucuronide and sulphate conjugates. These metabolites, previously characterized in our laboratory, were identified as being V1G, V2G, V3G and V4G for glucuronides and V1S, V2S, V3S, and V4S for sulphates ( Figure 1 ) [ 16 ]. The plasma and tissue concentration-time profiles of total glucuronides and of total sulphates are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study using rat liver extracts, we showed that the in vitro metabolism of ε-viniferin produced four glucuronides (V1G, V2G, V3G and V4G) and four sulphates (V1S, V2S, V3S and V4S), with glucuronides being the major metabolites. V2G and V3G represented more than 90% of the total glucuronides, whereas sulphates metabolites were present in equal proportion [ 16 ]. We now confirm the same metabolic profile in vivo in rat liver both for glucuronides and sulphates, which is an important finding ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After oral consumption, resveratrol is primarily metabolized by phase II enzymes, especially glucuronides and sulfatases, and absorbed in the small gut, predominantly in its glucuronidated form [ 12 , 56 ]. In addition to the glucuronide metabolite, sulfated products of resveratrol are also commonly found in biological samples [ 57 ]; however, only trace amounts of free resveratrol can be detected in plasma [ 58 ]. In this regard, Sergides et al [ 59 ] demonstrated higher plasma concentrations of glucuronidated (4083.9 ± 1704.4 ng/ml) and sulfated (1516.0 ± 639.0 ng/ml) resveratrol than its unmetabolized form (71.2 ± 42.4 ng/ml) following the consumption of a single resveratrol (500 mg) tablet in healthy volunteers.…”
Section: Resveratrol Plant Biosynthesis and Pharmacokineticsmentioning
confidence: 99%
“…For example, viniferin exhibited hepatoprotective activity and had a potent inhibitory effect against lipoxygenase and the oxidation of low-density lipoprotein and high-density lipoprotein [35]. It was also shown to prevent inflammation [36]. Furthermore, vinifirin was even identified as an anti-Alzheimer’s agent.…”
Section: Discussionmentioning
confidence: 99%